2000
DOI: 10.1038/sj.cdd.4400617
|View full text |Cite
|
Sign up to set email alerts
|

The fate of U1 snRNP during anti-Fas induced apoptosis: specific cleavage of the U1 snRNA molecule

Abstract: During apoptosis, the U1-70K protein, a component of the spliceosomal U1 snRNP complex, is specifically cleaved by the enzyme caspase-3, converting it into a C-terminally truncated 40-kDa fragment. In this study, we show that the 40-kDa U1-70K fragment is still associated with the complete U1 snRNP complex, and that no obvious modifications occur with the U1 snRNP associated proteins U1A, U1C and Sm-B/B'. Furthermore, it is described for the first time that the U1 snRNA molecule, which is the backbone of the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0

Year Published

2000
2000
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 48 publications
1
63
0
Order By: Relevance
“…The caspases activated during apoptosis cleave intracellular proteins into fragments that are bound by autoantibodies from some patients with LE (101,102). Further, proteins specifically phosphorylated during stress-induced apoptosis are tar-geted by antibodies from LE patient sera (103)(104)(105)(106). Granzyme B, a serine protease found principally in the cytotoxic granules of CTL and NK cells, can also cleave cellular autoantigens into unique fragments not detected in other forms of apoptosis.…”
Section: Increased Keratinocyte Apoptosis Formation Of Neo-antigensmentioning
confidence: 99%
“…The caspases activated during apoptosis cleave intracellular proteins into fragments that are bound by autoantibodies from some patients with LE (101,102). Further, proteins specifically phosphorylated during stress-induced apoptosis are tar-geted by antibodies from LE patient sera (103)(104)(105)(106). Granzyme B, a serine protease found principally in the cytotoxic granules of CTL and NK cells, can also cleave cellular autoantigens into unique fragments not detected in other forms of apoptosis.…”
Section: Increased Keratinocyte Apoptosis Formation Of Neo-antigensmentioning
confidence: 99%
“…During apoptosis, the U1-70K protein is specifically cleaved leading to the appearance of a 40 kDa fragment, 69,70 whereas the U1A, U1C and Sm-B/B' proteins are not detectably modified. 60,71 All proteins remain associated with the U1 snRNP complex in apoptotic cells. 71 The U1 snRNA molecule itself is a major target of autoimmunity in SLE-overlap syndromes, 72 and it has been shown that changes in the titer of anti-U1 snRNA autoantibodies may correlate with the severity of the disease.…”
Section: Modi®cations Of Small Structural Rnasmentioning
confidence: 99%
“…60,71 All proteins remain associated with the U1 snRNP complex in apoptotic cells. 71 The U1 snRNA molecule itself is a major target of autoimmunity in SLE-overlap syndromes, 72 and it has been shown that changes in the titer of anti-U1 snRNA autoantibodies may correlate with the severity of the disease. 73 The most immunodominant epitopes of the autoantigenic U1 snRNA molecule are located in stemloop II (nts 49 ± 65 and 76 ± 90) and stemloop IV (nts 150 ± 153), 74 and were recently characterized in more detail using several recombinant human monoclonal antibodies (scFvs).…”
Section: Modi®cations Of Small Structural Rnasmentioning
confidence: 99%
See 2 more Smart Citations